2020
DOI: 10.1159/000506321
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Painting Does Not Support a Sex Chromosome Turnover in Lacerta agilis Linnaeus, 1758

Abstract: Reptiles show a remarkable diversity of sex determination mechanisms and sex chromosome systems, derived from different autosomal pairs. The origin of the ZW sex chromosomes of Lacerta agilis, a widespread Eurasian lizard species, is a matter of discussion: is it a small macrochromosome from the 11-18 group common to all lacertids, or does this species have a unique ZW pair derived from the large chromosome 5? Using independent molecular cytogenetic methods, we investigated the karyotype of L. agilis exigua fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…prasina and Ta. dorsalis to this long list covering over 20% of currently recognized lacertid lizards [44]. Nevertheless, the data on the sequence content of the W chromosome and the cytogenetic identification of the Z chromosomes in lacertid karyotypes are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…prasina and Ta. dorsalis to this long list covering over 20% of currently recognized lacertid lizards [44]. Nevertheless, the data on the sequence content of the W chromosome and the cytogenetic identification of the Z chromosomes in lacertid karyotypes are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we selected the lizards of the family Lacertidae to explore the variability of the repetitive content of sex chromosomes between species across a wide phylogenetic scale in another model system. Previous cytogenetic studies demonstrated that all studied lacertids have highly differentiated ZZ/ZW sex chromosomes [34][35][36][37][38][39][40][41][42][43][44]. The majority of chromosomes in lacertids are acrocentric gradually decreasing in size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding leads to the prediction that the green iguana in the two studies showed different linkages of sex-chromosome systems based on turnover from another autosomal pair. However, this scenario is difficult to envisage because the results of chromosome painting do not support sex-chromosome turnover in lizards of Iguanoidea (Lisachov et al, 2020). An additional possibility might be an intraspecific polymorphism in sex-determination systems, as in the case of the Japanese wrinkled frog Glandirana rugosa (Ogata et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Given both scenarios of karyotype evolution proposed for neotropical boids, we carried out a cross-species chromosomal investigation performing chromosomal paintings in karyotypes of different Boidae species to decipher events of chromosome rearrangements associated with the evolutionary processes and diversification of this group. Cross-species chromosomal painting is a valuable comparative genomic tool in accessing and deciphering the dynamics of karyotype and genome evolution [ 31 , 32 , 33 ]. In this way, we used representative species of the genera Boa , Corallus , Eunectes , and Epicrates , covering all diploid numbers (2n = 36, 40 and 44) known for the family.…”
Section: Introductionmentioning
confidence: 99%